Bone lead associations with blood lead, kidney function and blood pressure among US, lead-exposed workers in a surveillance programme. Issue 5 (19th January 2019) - Barry, Vaughn; Todd, Andrew C; Steenland, Kyle
Abstract : Objectives: Bone lead and past blood lead levels may be more strongly associated with current health effects than current blood lead, representing recent exposure. We examined whether current bone lead was correlated with maximum past blood lead and compared how three lead measures predicted current blood pressure (BP) and kidney function among workers with past occupational lead exposure. Methods: Adult men in a lead surveillance programme residing near New York City were enrolled. Current bone and blood lead, BP and estimated glomerular filtration rate (eGFR) were measured. Maximum past blood lead was obtained from surveillance data. Regression models were used to determine associations of health with different lead measures. Results: Among 211 participants, median (IQR) bone, maximum past blood and current blood leads were 13.8 (9.4–19.5) µg lead per bone mineral gram, 29.0 (14.0–38.0) µg/dL and 2.5 (1.5–4.4) µg/dL, respectively. Maximum past and current blood lead were significantly associated with current bone lead in adjusted analyses (both p<0.0001), with associations driven by high blood lead. Bone lead was associated with increased continuous systolic BP (coefficient=0.36; 95% CI 0.05 to 0.67; p=0.02); categorical analyses indicated this was driven by the top two bone lead quartiles. Bone lead was non-significantly associated with decreased (worse) eGFR (coefficient=−0.15; 95% CI −0.36 to 0.07; p=0.18). Conclusions: Bone lead was significantly associated with past maximum and current blood lead. The association between bone and current blood lead was possibly driven by bone lead resorption into blood. Bone lead, but not past or current blood lead, was associated with elevated systolic BP.